2008
DOI: 10.3923/pjbs.2008.2336.2340
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Headspace CO2 Increases Biological Hydrogen Production by C. acetobutylicum

Abstract: The effect of removal of resultant gas resulted in enhancement of the H2 yield. The technique of CO2 scavenging resulted in H2 yield being improved from 408 mL g(-1) to reach the maximum of 422 mL g'. The highest hydrogen productivity of 87.9 ml L(-1) h(-1) was obtained by CO2 scavenging. Biomass concentration was enhanced to 1.47 g L(-1), Y(P,X) of 287 ml g(-1) L(-1), Y(X/S) of 0.294 and Y(H2/s) of 0.0377 by the use of CO2 scavenging. The results suggested that the presence of the gaseous products in fermenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Park et al 19 demonstrated that reducing the concentration of CO 2 from 24.5% into 5.3% in the headspace caused an increase in the hydrogen yield by 43%. Alshiyab et al 20 indicated that there is an increase in the hydrogen yield when the partial pressure of carbon dioxide is decreased.…”
Section: Experiments For Mass Transfer Of Co 2 With Microbubblesmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al 19 demonstrated that reducing the concentration of CO 2 from 24.5% into 5.3% in the headspace caused an increase in the hydrogen yield by 43%. Alshiyab et al 20 indicated that there is an increase in the hydrogen yield when the partial pressure of carbon dioxide is decreased.…”
Section: Experiments For Mass Transfer Of Co 2 With Microbubblesmentioning
confidence: 99%
“…For instance, the production of biohydrogen from glucose has been the subject of considerable investigation for the efficacy of gaseous product removal. normalC 6 normalH 12 normalO 6 + 2 normalH 2 normalO bacteria 2 normalC normalH 3 COOH + 2 CO 2 + 4 normalH 2 Tanisho et al found that hydrogen production increased when the partial pressure of CO 2 decreased. Park et al demonstrated that reducing the concentration of CO 2 from 24.5% into 5.3% in the headspace caused an increase in the hydrogen yield by 43%.…”
Section: Experiments For Mass Transfer Of Co2 With Microbubblesmentioning
confidence: 99%